Injury patterns of South African provincial cricket players over two seasons - Stretch, RA; Raffan, RP; Allan, N (South African Journal of Sports Medicine, 2009)
Objective. To determine the incidence and nature of injury patterns in elite cricketers over two seasons. Methods. Physiotherapists and/or doctors working with 4 provincial teams completed a questionnaire for each cricketer who presented with an injury during the 2004 - 2005 (S1) and 2005 - 2006 (S2) cricket seasons. This was done to determine: (i) the anatomical site of injury; (ii) the month of injury during the season; (iii) the diagnosis using the OSCIS injury classification system; (iv) the mechanism of injury; (v) whether it was a recurrence of a previous injury; (vi) whether the injury had recurred again during the season; and (vii) biographical data. Results. The results showed that 180 injuries (S1 – 84; S2 – 96) were sustained. On average the teams spent 2 472 hours on matches, 4 148 on practices and 1 612 on fitness training during the two-season period. The injury prevalence was 8% per match, while the injury incidence was 30/10 000 hours of match, practice and training time, with the match incidence being 74 injuries/ 10 000 hours and the training incidence 15 injuries/10 000 hours. Bowling (29%), fielding and wicket-keeping (27%) and batting (19%) accounted for the majority of injuries. The occurrence of injuries was predominantly to the lower limbs (S1 – 45%; S2 – 42%), back and trunk (S1 – 19%; S2 – 19%), upper limbs (S1 – 19%; S2 – 22%), head and neck (S1 – 6%; S2 – 3%), and related to illnesses (S1 – 11%; S2 – 14%). The injuries occurred primarily during first-class matches (39%), limited-overs matches (22%), and practices (17%), and some were of gradual onset (20%). Acute injuries comprised 78% of injuries. The majority of injuries were first-time injuries (76%), with 11% and 14% recurrent injuries from the previous and current seasons, respectively. The major injuries during S1 were haematomas (19%), muscle strains (17%) and other trauma (14%), while during S2 the injuries were primarily muscle strains (16%), other trauma (20%), tendinopathy (16%) and acute sprains (15%). The primary mechanisms of injury occurred in the delivery stride when bowling (19%) and overbowling (7%), on impact by the ball when batting (11%), and on sliding to field the ball (6%). Conclusion. The results indicate a pattern of cause of injury, with the fast bowler most likely to sustain an acute injury to the soft tissues of the lower limb while participating in matches and practices during the early part of the season.